Economic evaluation of aclidinium bromide in the management of moderate to severe COPD: an analysis over 5 years - Karabis A; Mocarski M; Eijgelshoven I; Bergman G (Dove Medical Press, 2014)
Andreas Karabis,1 Michelle Mocarski,2 Indra Eijgelshoven,1 Gert Bergman1 1Mapi HEOR and Strategic Market Access, Houten, the Netherlands; 2Forest Research Institute, Jersey City, NJ, USA Purpose: Aclidinium bromide is a long-acting muscarinic antagonistic used in maintenance treatment of chronic obstructive pulmonary disease (COPD). A model-based health economic study evaluated the cost-effectiveness of aclidinium 400 µg bid as an alternative to tiotropium 18 µg od for this indication in the US. Patients and methods: Patient characteristics in this model reflect those in the aclidinium clinical studies: age > 40 years, stable moderate-to-severe COPD, current or ex-smokers (>10 pack-years), post-salbutamol forced expiratory volume in 1 second (FEV1) ≥30% and <80% of predicted normal value, and FEV1/forced vital capacity <70%. The model consists of five main health states indicating severity of COPD and the level of utility, resource use, and costs. Treatment efficacy over 5 years was modeled using FEV1% predicted; a network meta-analysis comparing aclidinium and tiotropium was used to estimate disease progression during the first 24 weeks, and results from the UPLIFT trial were used for time points after 24 weeks. Quality of life was assessed using utility scores in US patients from the UPLIFT trial. Cost-effectiveness was assessed as the incremental cost per quality-adjusted life year (QALY) gained. Results: Over 5 years, QALYs were 3.50 for aclidinium versus 3.49 for tiotropium; life years accumulated were 4.52 for both. In this economic model, aclidinium versus tiotropium showed marginally fewer exacerbations (3.364 versus 3.390, respectively) and mean total health care costs (US$126,274 versus US$128,591, respectively). In all scenario analyses performed (discount factors of 0% and 6% for benefits and costs; time horizon of 1 year; mapping St George's Respiratory Questionnaire to European Quality of Life–5 Dimensions; excluding pharmacy costs, COPD-related cost only; cost of exacerbations; including ACCORD II trial in the network meta-analysis), aclidinium was associated with lower costs and marginally greater QALYs versus tiotropium. Conclusion: Aclidinium is potentially cost-effective compared with tiotropium for maintenance treatment of moderate-to-severe COPD. Keywords: chronic obstructive pulmonary disease, cost-effectiveness, model, tiotropium